Design and development of stabilized control systems for space application - Chia, Jie Xiang (Nanyang Technological University, 2020)
The focus of this project is to research on space control applications. As launching a satellite to space is more challenging than a High-Altitude Balloon (HAB), in this case, Near Space will be the main highlight in the design of this project. Work is done on the design and development of the control system that will be mounted on the payload of a HAB, where considerations such as weight, size and power requirements are paramount. The sensors used aim to experiment on valuable data such as Geiger counter for measuring gamma radiation and Chip Scale Atomic Clock (CSAC) for timing experiments. Also, additive manufacturing in the form of 3D printing will be explored as a means of rapid prototyping of CAD designs and preliminary testing. Also, since it is a quick and inexpensive means of fabrication, and weight is a factor of consideration in a HAB, thus the material used for the structure and mounts will be Polylactic Acid (PLA), a commonly used plastic filament in 3D printing. As for the control mechanism, a stabilised 3 degrees-of-freedom (3-DOF) gimbal will be attached under the sensor payload structure. The purpose is for video capturing using a commercially available sports action camera. Thus, the stabilization gimbal aims to reduce, as much as possible, the jittery & vibrational effects due to external disturbances such as wind and lift. The inability to eliminate is because wind speeds at higher altitudes can be stronger than what the gimbal can handle.